Preparation method of flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material

By introducing graphene and carbon nanotubes into MXene, flexible self-supporting thin film electrode materials are prepared, which solves the problem of easy stacking and oxidation of MXene, improves rate performance and electrochemical performance, and broadens the application fields.

CN118213206BActive Publication Date: 2025-01-03XIAN UNIV OF TECH

Patent Information

Application Number
CN202410428372.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2025-01-03
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

The easy stacking and oxidation of MXene two-dimensional nanosheets lead to poor rate performance in supercapacitors, limited electrolyte coverage area, and poor structural and oxidation stability, which limits its practical application prospects.

Method used

Introduce graphene and carbon nanotubes as intercalation materials, and prepare flexible self-supporting MXene/graphene/carbon nanotube thin film electrode materials through electrochemical peeling and ultrasonic dispersion technology to increase layer spacing, inhibit oxidation, improve active sites and electrochemistry performance.

Benefits of technology

It significantly improves the utilization rate and electrochemical performance of MXene materials, enhances the rate performance, improves the conductivity and mechanical strength, realizes high specific capacitance and stable ion transmission channels, and broadens the application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118213206B_ABST
    Figure CN118213206B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material, which comprises the following steps: ultrasonically dispersing exfoliated graphene in deionized water, centrifuging to form a graphene dispersion; adding functionalized carbon nanotubes to a polydiallyldimethylammonium chloride solution, ultrasonically dispersing, centrifuging and washing to obtain carbon nanotubes modified with polydiallyldimethylammonium chloride; mixing the MXene dispersion and the graphene dispersion, adding carbon nanotubes modified with polydiallyldimethylammonium chloride, ultrasonically crushing, stirring, vacuum filtering to form a film, freeze drying, and annealing. The introduction of graphene and carbon nanotubes suppresses the problem of easy stacking of MXene, increases active sites, promotes the diffusion of electrolyte ions, and improves electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode material preparation, and specifically relates to a method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material. Background Art

[0002] Among different types of energy storage systems, supercapacitors are considered to be a promising energy storage device due to their high power density, excellent stability and low cost. Due to the growing demand for portable and wearable electronic devices, high-performance supercapacitors with good flexibility have attracted the interest of researchers. Two-dimensional materials are easy to prepare into self-supporting thin film electrodes with excellent flexibility.

[0003] MXene is a metal carbide and nitride material with a two-dimensional layered structure. Thanks to its atomic layer thickness, excellent metal conductivity, good hydrophilicity and high redox activity, it is considered to be a very promising electrode material for flexible supercapacitors. However, the problem of easy stacking of MXene two-dimensional nanosheets reduces the exposure of active sites and hinders the transmission of electrolyte ions. Therefore, there are problems of poor rate performance and limited electrolyte coverage, especially when the loading level is high and solid gel is used as the electrolyte. In addition, its poor structure and oxidation stability will lead to a sharp decline in physical and chemical properties such as conductivity and mechanical strength, which seriously limits its practical application prospects. In order to solve these problems, it is necessary to introduce intercalation materials. Both carbon nanotubes and graphene have the advantages of high conductivity, high specific surface area, mechanical properties and excellent stability. Introducing graphene nanosheets and carbon nanotubes as intercalation materials into MXene nanosheets can increase the interlayer spacing of MXene, alleviate its stacking problem, improve the utilization rate of MXene materials, increase active sites, improve specific capacitance, and establish stable ion transmission channels to enhance rate performance. In addition, graphene, which is also a two-dimensional structure, is coated on the surface of MXene sheets and can inhibit the oxidation of MXene. Therefore, introducing graphene nanosheets and carbon nanotubes between MXene sheets to obtain self-supporting thin film electrode materials is an effective method for preparing flexible self-supporting electrodes for supercapacitors. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material. The introduction of graphene and carbon nanotubes inhibits the easy stacking and oxidation problems of MXene, increases active sites, and is beneficial to improving the electrochemical properties of the material.

[0005] The technical solution adopted by the present invention is a method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material, which is specifically implemented according to the following steps:

[0006] Step 1, preparing a MXene dispersion;

[0007] Step 2, preparing exfoliated graphene;

[0008] Step 3, ultrasonically dispersing the exfoliated graphene in deionized water, and centrifuging to form a graphene dispersion;

[0009] Step 4, adding the functionalized carbon nanotubes into the polydiallyldimethylammonium chloride solution, ultrasonically dispersing, centrifuging and washing to obtain the polydiallyldimethylammonium chloride modified carbon nanotubes;

[0010] Step 5: Mix the MXene dispersion and the graphene dispersion, add carbon nanotubes modified with polydiallyldimethylammonium chloride, crush with an ultrasonic crusher, stir magnetically, vacuum filter to form a film, freeze-dry, and anneal to obtain a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material.

[0011] The present invention is also characterized in that:

[0012] In step 1, specifically:

[0013] After HCl and deionized water are mixed and stirred, LiF is added, and a hydrofluoric acid solution is prepared by magnetic stirring; Ti3AlC2 is added to the hydrofluoric acid solution and magnetically stirred; the liquid is centrifuged and washed until neutral, ultrasonicated and centrifuged several times, and the upper layer of liquid is taken to obtain a MXene dispersion.

[0014] In step 2, specifically:

[0015] Graphite foil is used as a carbon electrode, i.e., an anode, and a platinum wire is used as a cathode for electrochemical exfoliation of graphite. The graphite foil and the platinum electrode are placed in a 0.1-1M MgSO4 electrolyte, and then electrochemical exfoliation is performed by applying a positive voltage of 8-10V to the graphite electrode. After the graphite exfoliation is completed, the product is vacuum filtered with deionized water to obtain exfoliated graphene.

[0016] In step 3, the ultrasonic time is 20 min, the centrifugal speed is 3000 r / min, and the centrifugal time is 20 min; the concentration of the graphene dispersion is 0.5-3 mg / mL.

[0017] In step 4, the functionalized carbon nanotubes are hydroxyl or carboxyl multi-walled carbon nanotubes, the mass ratio of the functionalized carbon nanotubes to the polydiallyldimethylammonium chloride solution is 1:3-6, the concentration of the polydiallyldimethylammonium chloride solution is 0.3-1.0wt.%, and the ultrasonic dispersion time is 5-8h.

[0018] In step 5, the power of the ultrasonic cell pulverizer is 250-300 W, the pulverization time is 10-20 min; and the magnetic stirring time is 4-6 h.

[0019] In step 5, the annealing conditions are: in an inert atmosphere of nitrogen or argon, the temperature is raised to 200-600° C. at a rate of 2-5° C. / min and kept for 1 hour; the freeze-drying temperature is -40° C. and the time is 24-36 hours.

[0020] The beneficial effects of the present invention are:

[0021] 1) The method of the present invention prepares a flexible self-supporting composite electrode material (MGC) by mixing highly dispersible MXene, electrochemically exfoliated graphene, and carbon nanotubes modified with polydiallyldimethylammonium chloride through self-assembly and vacuum-assisted filtration. MXene has excellent metallic conductivity, good hydrophilicity, and high redox activity. The introduction of graphene and carbon nanotubes inhibits the easy stacking problem of MXene, increases active sites, promotes the diffusion of electrolyte ions, and improves electrochemical performance; two-dimensional graphene is coated on the surface of MXene sheets to inhibit the oxidation of MXene; the prepared MXene / graphene / carbon nanotube flexible self-supporting composite film is used as an electrode, and 1mA cm -2 At the current density, its area specific capacity reaches 1862.5mF cm -2 ;

[0022] 2) The electrostatic interaction between MXene and poly(diallyldimethylammonium chloride)-modified carbon nanotubes ensures good interfacial interaction and complete electron transport channels;

[0023] 3) The method of the present invention does not use a current collector and a binder, which saves costs, avoids the problems of adhesion and poor conductivity of the current collector during the use cycle, and the fact that neither the current collector nor the binder contributes to the specific capacitance, and also achieves flexibility, broadening the application field;

[0024] 4) In the method of the present invention, the reaction conditions for preparing graphene by electrochemical exfoliation are easy to achieve, mild and easy to control, and the prepared graphene does not require reduction treatment. It also has the advantage of high dispersibility, which is conducive to the preparation of composite films;

[0025] 5) In the method of the present invention, the annealing treatment of the film under an inert atmosphere can remove the functional groups on the surface of MXene and graphene, improve the conductivity, and thus benefit the electrochemical performance;

[0026] 6) The materials and reagents used in the method of the present invention are easily available, non-toxic and harmless, the process is simple, and it is easy to prepare in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The transmission electron microscope image of the graphene obtained by electrochemical exfoliation and the photograph of the graphene dispersion after being placed for 3 weeks;

[0028] Figure 2 This is a scanning electron microscope image of the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of Example 2;

[0029] Figure 3 The nitrogen adsorption-desorption isotherms and pore size distribution curves of the materials of Examples 1 and 2 are shown;

[0030] Figure 4 is a nitrogen adsorption-desorption isotherm and pore size distribution curve of the material of Example 3;

[0031] Figure 5 This is a cyclic voltammetric characteristic curve of the materials in Examples 1 and 2 and the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material in Example 1;

[0032] Figure 6 It is a constant current charge and discharge curve diagram of the materials of Examples 1 and 2 and the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of Example 2;

[0033] Figure 7 This is a rate performance diagram of the materials in Examples 1 and 2 and the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material in Example 3. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with specific implementation modes and accompanying drawings.

[0035] The method for preparing the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of the present invention is specifically implemented according to the following steps:

[0036] Step 1, preparing a MXene dispersion;

[0037] Specifically, HCl and deionized water are mixed and stirred, and then LiF is added, and a hydrofluoric acid solution is prepared by magnetic stirring; Ti3AlC2 is added to the hydrofluoric acid solution and magnetically stirred; the liquid is centrifuged and washed to neutrality, ultrasonicated and centrifuged several times, and the upper layer of liquid is taken to obtain a MXene dispersion;

[0038] The volume ratio of HCl to deionized water was 3:1; HCl and deionized water were mixed and stirred for 5 min, and after adding LiF, the magnetic stirring time was 30 min, and the temperature was 35°C; the mass ratio of LiF to Ti3AlC2 was 1:1;

[0039] After adding Ti3AlC2, the magnetic stirring temperature is 35°C and the stirring time is 24 to 30 h;

[0040] The centrifugal speed is 3500r / min, the centrifugal time is 5min, and the ultrasonic time is 10-20min;

[0041] Step 2: Using graphite foil as a carbon electrode, i.e., an anode, and platinum wire as a cathode, for electrochemical exfoliation of graphite, placing the graphite foil and the platinum electrode in a 0.1-1M MgSO4 electrolyte, and then applying a positive voltage of 8-10V to the graphite electrode for electrochemical exfoliation. After the graphite exfoliation is completed, the product is vacuum filtered with deionized water to obtain exfoliated graphene;

[0042] Step 3, dispersing the exfoliated graphene in deionized water, performing ultrasound treatment, and centrifuging to form a graphene dispersion;

[0043] The ultrasonic time is 20 min, the centrifugal speed is 3000 r / min, and the centrifugal time is 20 min; the concentration of the graphene dispersion is 0.5-3 mg / mL.

[0044] The process of electrochemical exfoliation of graphene in an inorganic salt electrolyte is easy to control and has high efficiency. The graphene produced has low oxygen content, good conductivity, and does not require reduction.

[0045] Step 4: adding the functionalized carbon nanotubes into the polydiallyldimethylammonium chloride solution, dispersing by ultrasonication, and obtaining the polydiallyldimethylammonium chloride-modified carbon nanotubes by centrifugation and washing.

[0046] The functionalized carbon nanotubes are hydroxyl or carboxyl multi-walled carbon nanotubes, the mass ratio of the functionalized carbon nanotubes to the polydiallyldimethylammonium chloride solution is 1:3-6, the concentration of the polydiallyldimethylammonium chloride solution is 0.3-1.0wt.%, and the ultrasonic dispersion time is 5-8h.

[0047] Step 5: Mix the MXene dispersion and the graphene dispersion, add the carbon nanotubes modified with polydiallyldimethylammonium chloride, crush with an ultrasonic crusher, stir with a magnetic force, vacuum filter the obtained mixture to form a film, freeze-dry, and anneal to obtain a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material;

[0048] The power of the ultrasonic cell crusher is 250-300W, and the crushing time is 10-20min; the magnetic stirring time is 4-6h;

[0049] Annealing conditions are: in an inert atmosphere of nitrogen or argon, heating to 200-600°C at a rate of 2-5°C / min and keeping at that temperature for 1h;

[0050] The freeze-drying temperature is -40°C and the time is 24 to 36 hours;

[0051] The mass ratio of MXene, electrochemically exfoliated graphene and polydiallyldimethylammonium chloride modified carbon nanotubes is 6:1~3:0.5~1.

[0052] Based on its excellent metallic conductivity, good hydrophilicity and high redox activity, MXene is considered to be a very promising electrode material for flexible supercapacitors. However, it has the problems of easy stacking and easy oxidation. Introducing electrochemically exfoliated graphene nanosheets with good dispersion and carbon nanotubes modified with positively charged polydiallyldimethylammonium chloride as intercalation materials into MXene nanosheets can increase the interlayer spacing of MXene, alleviate its stacking problem, improve the utilization of MXene, increase active sites, increase specific capacitance, and establish stable ion and electron transmission channels to enhance rate performance. In addition, graphene, which is also a two-dimensional structure, is coated on the surface of MXene sheets, which can alleviate the oxidation of MXene. Under the synergistic effect of the three, a flexible self-supporting electrode material with excellent electrochemical performance is obtained.

[0053] Comparative Example 1

[0054] The preparation method of MXene flexible thin film electrode material is specifically as follows: after mixing HCl and deionized water in a volume ratio of 3:1 and stirring for 5 minutes, LiF is added, and hydrofluoric acid is prepared by magnetic stirring at 35°C for 30 minutes; Ti3AlC2 is added in a mass ratio of 1:1, and magnetic stirring is performed at 35°C for 26 hours, and centrifugal washing is repeated at 3500r / min until neutral, and then it is first ultrasonicated and then centrifuged, and the upper layer liquid is taken as the MXene dispersion liquid, vacuum filtered to form a film, freeze-dried for 24 hours, and then heated to 400°C at 5°C / min in a nitrogen atmosphere and kept warm for 1 hour, and the MXene flexible thin film electrode material can be obtained after cooling.

[0055] Comparative Example 2

[0056] The preparation method of MXene / graphene flexible thin film electrode material is as follows: HCl and deionized water with a volume ratio of 3:1 are mixed and stirred for 5 minutes, then LiF is added, and hydrofluoric acid is prepared by magnetic stirring at 35°C for 30 minutes; Ti3AlC2 with a mass ratio of 1:1 is added, and magnetic stirring is performed at 35°C for 26 hours, and centrifugal washing is repeated at 3500r / min until neutral, and then it is first ultrasonicated and then centrifuged to take the upper layer liquid as MXene dispersion liquid; graphite foil is used as a carbon electrode, i.e., an anode, and platinum wire is used as a cathode for electrochemical exfoliation of graphite, and the graphite foil and the platinum electrode are placed in 0.1M MgSO4 solution, then electrochemically exfoliate by applying a 10V positive voltage to the graphite electrode. After the graphite exfoliation is completed, the product is vacuum filtered with deionized water to obtain exfoliated graphene; the exfoliated graphene is dispersed in deionized water, ultrasonicated for 20 minutes, and then centrifuged at 3000r / min for 20 minutes to form a graphene dispersion; after the single-layer MXene dispersion and the graphene dispersion are mixed, ultrasonically crushed at 300W power for 10 minutes and magnetically stirred for 6 hours; then the mixed liquid is vacuum filtered to form a film, freeze-dried for 30 hours, and then heated to 400℃ at 5℃ / min in a nitrogen atmosphere for 1 hour. After cooling, the MXene / graphene flexible film electrode material can be obtained, which is recorded as MG. The mass ratio of MXene to graphene is 6:3.

[0057] Example 1

[0058] The preparation method of the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of the present invention is specifically as follows:

[0059] HCl and deionized water in a volume ratio of 3:1 were mixed and stirred for 5 minutes, and then LiF was added, and hydrofluoric acid was prepared by magnetic stirring at 35°C for 30 minutes; Ti3AlC2 in a mass ratio of 1:1 was added, and magnetic stirring was performed at 35°C for 26 hours, and centrifugal washing was repeated at 3500r / min until neutral, and then it was first ultrasonicated and then centrifuged, and the upper layer liquid was taken as MXene dispersion; graphite foil was used as carbon electrode, i.e. anode, and platinum wire was used as cathode for electrochemical exfoliation of graphite. The graphite foil and platinum electrode were placed in 0.1M The invention relates to a method for preparing a graphene dispersion comprising the steps of: dispersing the graphene in deionized water, ultrasonicating the graphene for 20 minutes, and centrifuging the graphene at 3000 r / min for 20 minutes to form a graphene dispersion; weighing 50 mg of hydroxy carbon nanotubes, adding the mixture to 150 mL of a 1 wt.% polydiallyldimethylammonium chloride solution, ultrasonically dispersing the mixture for 6 hours, and obtaining polydiallyldimethylammonium chloride-modified carbon nanotubes by centrifugation and washing; mixing a monolayer MXene dispersion and a graphene dispersion, adding carbon nanotubes, ultrasonically crushing the mixture at 300 W for 10 minutes, and magnetically stirring the mixture for 6 hours. The mixed dispersion is then vacuum filtered to form a film, freeze-dried for 36 hours, and then heated to 400°C at 5°C / min in a nitrogen atmosphere for 1 hour, and then cooled to obtain a MXene / graphene / carbon nanotube flexible self-supporting electrode material. The mass ratio of MXene, graphene and carbon nanotubes is 6:3:1.

[0060] Example 2

[0061] The preparation method of the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of the present invention is specifically as follows:

[0062] HCl and deionized water in a volume ratio of 3:1 were mixed and stirred for 5 minutes, and then LiF was added, and hydrofluoric acid was prepared by magnetic stirring at 35°C for 30 minutes; Ti3AlC2 in a mass ratio of 1:1 was added, and magnetic stirring was performed at 35°C for 24 hours, and centrifugal washing was repeated at 3500r / min until neutral, and then it was first ultrasonicated and then centrifuged, and the upper layer liquid was taken as MXene dispersion liquid; graphite foil was used as carbon electrode, i.e. anode, and platinum wire was used as cathode for electrochemical exfoliation of graphite, and the graphite foil and platinum electrode were placed in 1M MgSO4 solution, and then electrochemically exfoliate by applying 8V positive voltage to the graphite electrode. After the graphite exfoliation is completed, the product is vacuum filtered with deionized water to obtain exfoliated graphene; the exfoliated graphene is dispersed in deionized water, ultrasonicated for 20 minutes, and then centrifuged at 3000r / min for 20 minutes to form a graphene dispersion; 50mg of hydroxy carbon nanotubes are weighed and added to 300mL of 0.3wt.% polydiallyldimethylammonium chloride solution, ultrasonically dispersed for 6h, and centrifuged. , washing to obtain polydiallyldimethylammonium chloride modified carbon nanotubes; after mixing the monolayer MXene dispersion and graphene dispersion, add carbon nanotubes, ultrasonically crush at 250W for 15min and magnetically stir for 4h; then vacuum filter the mixed liquid to form a film, freeze-dry for 30h, heat to 200℃ at 2℃ / min in argon atmosphere for 1h, and cool to obtain MXene / graphene / carbon nanotube flexible self-supporting electrode material. The mass ratio of MXene, graphene and carbon nanotubes is 6:2:1.

[0063] Example 3

[0064] The preparation method of the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of the present invention is specifically as follows:

[0065] HCl and deionized water in a volume ratio of 3:1 were mixed and stirred for 5 minutes, and then LiF was added, and hydrofluoric acid was prepared by magnetic stirring at 35°C for 30 minutes; Ti3AlC2 in a mass ratio of 1:1 was added, and magnetic stirring was performed at 35°C for 30 hours, and centrifugal washing was repeated at 3500r / min until neutral, and then it was ultrasonicated and then centrifuged to take the upper layer liquid as MXene dispersion liquid; graphite foil was used as carbon electrode, i.e. anode, and platinum wire was used as cathode for electrochemical exfoliation of graphite. The graphite foil and platinum electrode were placed in 0.5M The graphite was then electrochemically stripped by applying a positive voltage of 8.5 V to the graphite electrode. After the graphite was stripped, the product was vacuum filtered with deionized water to obtain exfoliated graphene. The exfoliated graphene was dispersed in deionized water, ultrasonicated for 20 minutes, and then centrifuged at 3000 r / min for 20 minutes to form a graphene dispersion. 50 mg of hydroxy carbon nanotubes were weighed and added to 200 mL of a 0.5 wt.% polydiallyldimethylammonium chloride solution, ultrasonically dispersed for 6 hours, and centrifuged. The carbon nanotubes modified with polydiallyldimethylammonium chloride were prepared by washing; the monolayer MXene dispersion and graphene dispersion were mixed, and then carbon nanotubes were added, ultrasonically crushed at 280W for 20 minutes, and then magnetically stirred for 5 hours; the mixed liquid was then vacuum filtered to form a film, freeze-dried for 28 hours, and then heated to 400℃ at 3℃ / min in an argon atmosphere for 1 hour, and then cooled to obtain MXene / graphene / carbon nanotube flexible film electrode materials. The mass ratio of MXene, graphene and carbon nanotubes is 6:1:0.5;

[0066] Figure 1 The transmission electron microscope image of graphene obtained by electrochemical exfoliation in Example 1, and the inset image is a high-resolution transmission electron microscope image and a real photo of the graphene dispersion after being placed for 3 weeks. The results show that the graphene presents a transparent and ultra-thin nanosheet morphology, and has good dispersibility and stability, which is conducive to the preparation of the composite electrode; Figure 2 This is a scanning electron microscope image of the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material of Example 2, showing that carbon nanotubes are interspersed between MXene nanosheets and graphene sheets. Figure 3 , 4 The nitrogen adsorption-desorption isotherms and pore size distribution curves of the comparative example and Example 3 are shown in Figure 1. It can be seen that the introduction of graphene and carbon nanotubes increases the mesopores, which facilitates the diffusion of electrolyte ions. The average pore size, pore volume and specific surface area of ​​the MXene / graphene / carbon nanotube film of Example 3 are increased from 3.786 nm and 0.088 cm of MXene, respectively. 3 g -1 and 93.088m 2 g -1 Increased to 9.982nm, 0.276cm3 g -1 and 112.259m 2 g -1 The flexible thin film electrode materials prepared in the comparative example and Examples 1-3 were used as self-supporting electrodes, platinum electrodes and Hg / HgO electrodes were used as auxiliary electrodes and reference electrodes respectively, and PVA / H3PO4 gel was used as electrolyte. The three-electrode electrochemical performance was tested on a Coster electrochemical workstation. Figure 5 The results of Example 1 and Comparative Examples 1 and 2 at 10 mV s -1 In the cyclic voltammetry characteristic curve under the scanning rate, the MGC membrane electrode has the largest CV curve closed area, indicating that the MGC membrane electrode has the best charge storage capacity. Figure 6 The results of Example 2 and Comparative Examples 1 and 2 at 1 mA cm -2 The constant current charge and discharge curve under the current density shows that the MGC membrane electrode of Example 2 has the largest GCD discharge time, indicating that the flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material has the largest specific capacitance. Figure 7 The rate performance of Example 3 and Comparative Examples 1 and 2 is the same. The MGC membrane electrode exhibits the best charge storage capacity, which is due to the introduction of graphene and carbon nanotubes. For the MGC membrane electrode, the charge storage capacity is 1, 2, 3, 5, 10, 15 and 20 mA cm -2 At the current density, the area specific capacitance is 1862.5, 1675, 1670.5, 1637.5, 1630, 1600 and 1525 mF cm -2 When the current density increases from 1 mA cm -2 Increase to 20mA cm -2 The capacitance retention rate is as high as 81.88%, indicating that the MGC membrane electrode has excellent rate performance.

Claims

1. A method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material, characterized in that: Follow the steps below to implement it: Step 1, preparing a MXene dispersion; Step 2, preparing exfoliated graphene; Step 3, ultrasonically dispersing the exfoliated graphene in deionized water, and centrifuging to form a graphene dispersion; Step 4, adding the functionalized carbon nanotubes into the polydiallyldimethylammonium chloride solution, ultrasonically dispersing, centrifuging and washing to obtain the polydiallyldimethylammonium chloride modified carbon nanotubes; The functionalized carbon nanotubes are hydroxyl or carboxyl multi-walled carbon nanotubes, the mass ratio of the functionalized carbon nanotubes to the polydiallyldimethylammonium chloride solution is 1:3-6, the concentration of the polydiallyldimethylammonium chloride solution is 0.3-1.0 wt.%, and the ultrasonic dispersion time is 5-8 h; Step 5: Mix the MXene dispersion and the graphene dispersion, add carbon nanotubes modified with polydiallyldimethylammonium chloride, crush with an ultrasonic crusher, stir magnetically, vacuum filter to form a film, freeze-dry, and anneal to obtain a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material; The annealing conditions are as follows: in an inert atmosphere of nitrogen or argon, the temperature is raised to 200-600°C at a rate of 2-5°C / min and kept for 1 hour; the freeze-drying temperature is -40°C and the time is 24-36 hours.

2. The method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material according to claim 1, characterized in that: In the step 1, specifically: After HCl and deionized water are mixed and stirred, LiF is added, and a hydrofluoric acid solution is prepared by magnetic stirring; Ti3AlC2 is added to the hydrofluoric acid solution and magnetically stirred; the liquid is centrifuged and washed until neutral, ultrasonicated and centrifuged several times, and the upper layer of liquid is taken to obtain a MXene dispersion.

3. The method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material according to claim 1, characterized in that: In the step 2, specifically: Graphite foil is used as a carbon electrode, i.e., an anode, and a platinum wire is used as a cathode for electrochemical exfoliation of graphite. The graphite foil and the platinum electrode are placed in a 0.1~1M MgSO4 electrolyte, and then electrochemical exfoliation is performed by applying a positive voltage of 8~10 V to the graphite electrode. After the graphite exfoliation is completed, the product is vacuum filtered with deionized water to obtain exfoliated graphene.

4. The method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material according to claim 1, characterized in that: In the step 3, the ultrasonic time is 20 min, the centrifugal speed is 3000 r / min, and the centrifugal time is 20 min; the concentration of the graphene dispersion is 0.5-3 mg / mL.

5. The method for preparing a flexible self-supporting MXene / graphene / carbon nanotube thin film electrode material according to claim 1, characterized in that: In step 5, the power of the ultrasonic cell pulverizer is 250-300 W, the pulverization time is 10-20 min, and the magnetic stirring time is 4-6 h.

Citation Information

Patent Citations

  • Negative material, negative plate, battery assembly and preparation methods

    CN110299529A

  • Layer-by-layer self-assembly composite conductive fiber bundle and preparation method thereof

    CN111636195A

Cited By

  • Super capacitor

    CN121641698A

  • A supercapacitor

    CN121641698B